(untitled) (Swiss Medical Weekly, 2014)
INTRODUCTION: It is recognised that vitamin D status is often inadequate (<50 nmol/l) in epileptic children, mainly because some anticonvulsant drugs induce the enzymes responsible for its metabolism. The purpose of the present study was to address vitamin D status among children and adolescents treated with anticonvulsant drugs and control subjects who reside in southern Switzerland, a high solar radiation region. METHODS: Between January and May 2013, total serum 25-hydroxyvitamin D was assessed by liquid chromatography-tandem mass spectrometry in 58 children and adolescents with epilepsy and 29 controls residing in southern Switzerland. Dark-skinned individuals, females wearing dress styles covering practically the whole body and subjects with body mass index ≥85th percentile for age and sex were excluded. RESULTS: Concentration of serum 25-hydroxyvitamin D was similar in epilepsy patients (48 [37–62] nmol/l; median and interquartile range) and controls (53 [47–64] nmol/l). An inadequate serum 25-hydroxyvitamin D concentration was common both among patients (55%) and control subjects (34%). Serum 25-hydroxyvitamin D was significantly lower among patients treated with anticonvulsant drugs that induce the metabolism of vitamin D (30 [21–51] nmol/l) than among the remaining patients (51 [40–65] nmol/l) and controls. CONCLUSIONS: The present study indicates a relevant tendency towards inadequate vitamin D status among children with and without anticonvulsant drug management who reside in southern Switzerland. This tendency is more prominent in patients treated with anticonvulsant drugs that induce the metabolism of 25-hydroxyvitamin D.